Liquid Biopsy-Driven Cetuximab Rechallenge Strategy in Molecularly Selected Metastatic Colorectal Cancer Patients - Mariani, Stefano; Puzzoni, Marco; Giampieri, Riccardo; Ziranu, Pina; Pusceddu, Valeria; Donisi, Clelia; Persano, Mara; Pinna, Giovanna; Cimbro, Erika; Parrino, Alissa; Spanu, Dario; Pretta, Andrea; et al. (Frontiers in Oncology, 2022)
Background: Rechallenge with EGFR inhibitors represents a promising strategy for patients with RAS wild type (WT) colorectal cancer (CRC) but definitive selection criteria are lacking. Recently the RAS WT status on circulating tumor DNA (ct-DNA) emerged as a potential watershed for this strategy. Our study explored the liquid biopsy driven cetuximab rechallenge in a RAS and BRAF WT selected population. Methods: CRC patients with RAS and BRAF WT both on tumor tissue and on ct-DNA at baseline receiving rechallenge with cetuximab were eligible for our analysis. Ct-DNA was analyzed for RAS-BRAF mutations with pyro-sequencing and nucleotide sequencing assays. Real-time PCR and droplet digital PCR were performed to confirm the RAS-BRAF mutational status. Results: A total of 26 patients were included in our analysis. In the global population RR was 25.0%, median overall survival (mOS) was 5.0 months, median progression free survival (mPFS) was 3.5 months. Previous response to anti-EGFR was associated with improved mPFS (5.0 vs 2.0 months,HR:0.26,p:0.048), anti-EGFR free interval>14 months and anti-EGFR free interval>16 months were associated with improved mPFS (respectively 7.0 vs 3.0 months, HR:0.27, p:0.013 and not reached vs 3.0 months, HR:0.20, p:0.002) and with improved mOS (respectively 13.0 vs 5.0 months, HR:0.27, p:0.013 and 13.0 vs 5.0 months, HR:0.20, p: 0.002). Previous lines>2 were correlated with improved mPFS (4.0 vs 1.0, HR:0.05, p: 0.041) and with improved mOS (7.0 vs 1.0 months, HR:0.045, p:0.034). In a multiple logistic regression model only the anti-EGFR free interval was confirmed to be a significant predictor for mOS and mPFS. Conclusions: Liquid biopsy driven cetuximab rechallenge confirmed to be effective. The clinical outcome resulted consistent with available results from phase 2 studies. In addition to the molecular selection through the analysis of ct-DNA for RAS, the long anti-EGFR free interval is confirmed as a prospective selection criterion for this therapeutic option.